The impact of the covalently closed circular DNA level on recurrence of hepatocellular carcinoma after initial hepatectomy: an analysis of patients with resolved hepatitis B virus infection. Issue 10 (October 2022) - Bae, Sung Kwan; Arita, Junichi; Akamatsu, Nobuhisa; Maki, Harufumi; Nishioka, Yujiro; Kawahara, Takuya; Miyata, Akinori; Kokudo, Takashi; Nagata, Rihito; Mihara, Yuichiro; Ichida, Akihiko; Inagaki, Yoshinori; et al.
Abstract: Background: We assessed whether or not covalently closed circular DNA (cccDNA) levels in the background liver influence the recurrence of hepatocellular carcinoma (HCC) in patients with resolved hepatitis B virus (HBV) infection. Methods: Among 425 patients who underwent initial hepatectomy for HCC between 2010 and 2018, a retrospective review was performed in 44 with resolved HBV infection. The clinicopathologic characteristics were analyzed for correlation with tumor recurrence. The HBV cccDNA levels were tested via a droplet digital polymerase chain reaction assay. Results: HBV cccDNA was detected in 27 of 44 patients (61%), and the median level was 1.0 copies/1000 ng (range, 0-931.3 copies/1000 ng). Anti-HBc ≥8.9 S/CO was associated with cccDNA detection (odds ratio, 11.08; 95% confidence interval [95% CI], 2.48-49.46; P = 0.002). Twenty-eight patients (64%) developed HCC recurrence after hepatectomy. The overall 3- and 5-year recurrence-free survival rates were 45.7% and 34.3%, respectively.19 HBV cccDNA levels was not significantly associated with HCC recurrence, while the presence of multiple tumors was an independent risk fact or (hazard ratio, 6.53; 95% CI, 2.48-17.19; P < 0.001. Conclusion: HBV cccDNA levels did not influence HCC recurrence after hepatectomy. Anti-HBc levels may be used as a surrogate marker for cccDNA.